Comparative Study of the Routine Daily Usability of FoodLog: A Smartphone-based Food Recording Tool Assisted by Image Retrieval. (March 2014) - Aizawa, Kiyoharu; Maeda, Kazuki; Ogawa, Makoto; Sato, Yohei; Kasamatsu, Mayumi; Waki, Kayo; Takimoto, Hidemi
The health care field is focusing considerable attention on dietary control, which requires that individuals record what they eat. We have developed a novel smartphone application called FoodLog, a multimedia food recording tool that allows users to take photos of their meals and to produce textual food records. Unlike conventional smartphone-based food recording tools, FoodLog allows users to employ meal photos to help them to input textual descriptions based on image retrieval. In this study, we conducted usability experiments to evaluate the routine daily use of FoodLog systems with and without image-based assistance. We produced 2 food recording tools: FoodLog with image-based assistance (FL-I) and FoodLog with text input only (FL-T). We recruited 18 university students (age = 18-24 years), all of whom performed food recording for the first time. The participants used FoodLog on a daily basis for 1 month. In the subjective evaluation, FL-I had higher average scores for questions related to ease of use, fun, frequency of browsing, and intention to continue. In particular, the latter 3 factors received significantly higher scores with FL-I than with FL-T. In the quantitative evaluation, the daily average number of meal events and food records did not differ significantly between FL-I and FL-T. A detailed analysis of the individual records showed that 1 participant produced 3 times as many records using FL-I compared with FL-T. The subjective assessment showed that our new tool, which fully exploits the use of images, is a promising method for food recording.